Muslim Women as Environmental Warriors: A Study of Nahdliyin Women's Social Networks in the Ecological Jihad Movement in Indonesia - Imam, Khoirul; Millah, Ahmad Sihabul (AN NUR: Jurnal Studi Islam, 2024)
This study explicitly fills the gaps in studies related to women, Islam, and the environment from a social network perspective. In carrying out their movement, Nahdliyin women use a social network model divided into three clusters: the power, emotional, and interest networks. Researchers will see the extent to which the network pattern runs effectively in launching its vision and mission. This research is qualitative and uses an analytical descriptive method. The results of this study are that the social network model used is quite successful in the development, sustainability, and sustainability of institutions, in particular, and in general, is able to contribute to environmental conservation and plastic waste reduction despite having to face various challenges from various groups.